2015
DOI: 10.1016/j.ajpath.2015.01.033
|View full text |Cite|
|
Sign up to set email alerts
|

SIV Encephalitis Lesions Are Composed of CD163+ Macrophages Present in the Central Nervous System during Early SIV Infection and SIV-Positive Macrophages Recruited Terminally with AIDS

Abstract: Macrophage recruitment to the central nervous system (CNS) during AIDS pathogenesis is poorly understood. We measured the accumulation of brain perivascular (CD163 þ ) and inflammatory (MAC387 þ ) macrophages in SIV-infected monkeys. Monocyte progenitors were 5-bromo-2 0 -deoxyuridine (BrdU) labeled in bone marrow, and CNS macrophages were labeled serially with fluorescent dextrans injected into the cisterna magna. MAC387 þ macrophages accumulated in the meninges and choroid plexus in early inflammation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 91 publications
6
54
0
3
Order By: Relevance
“…The findings of Nowlin et al 3 are of great interest to CNS macrophage biologists as well as immunologists studying acute and chronic inflammation. Early during SIV infection, Nowlin et al 3 reported most cells to be MAC387 þ recently recruited monocytes/macrophages.…”
Section: Study Outcomementioning
confidence: 99%
See 4 more Smart Citations
“…The findings of Nowlin et al 3 are of great interest to CNS macrophage biologists as well as immunologists studying acute and chronic inflammation. Early during SIV infection, Nowlin et al 3 reported most cells to be MAC387 þ recently recruited monocytes/macrophages.…”
Section: Study Outcomementioning
confidence: 99%
“…Nowlin et al 3 used straightforward multilabel immunohistochemical approaches to assess macrophage populations and their turnover in the choroid plexus, meninges, perivascular space, and parenchymal lesions (when present in animals with SIVE). The method also allowed comparison of the rates of turnover in early acute inflammation and in the later inflammation as the animals developed AIDS and CNS lesions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations